Efektivitas Terapi Relaksasi Otot Progresif dan Terapi Musik Suara Alam Terhadap Tingkat Stres Mahasiswa Semester Akhir: Effectiveness of Progressive Muscle Relaxation Therapy and Natural Sound Music Therapy on Final Semester Student Stress Levels - Cahyani, Ardhia Redina; Tasalim, Rian (LPPM STIKES Guna Bangsa, 2024)
Final year students have academic interests such as a lot of assignments and have many demands from themselves and from external demands which causes students to be more susceptible to experiencing stress. Prolonged and untreated stress can cause physical and psychological disorders. Stress can be treated pharmacologically and non-pharmacologically. There are several non-pharmacological ways that can be done to reduce stress levels, namely progressive muscle relaxation therapy and music therapy. This research generally aims to determine the effect of progressive muscle relaxation therapy and natural sound music therapy on the stress levels of final semester students. This research uses a quantitative approach using a pre-experimental design. The total sample was 8 people taken using accidental sampling technique, based on inclusion and exclusion criteria. The data collection technique uses the PSS questionnaire. The analysis used the Wilcoxon test. The results of the bivariate test showed that there was an effect of progressive muscle relaxation techniques and natural sound music therapy on the stress level of final semester students with a significant value of 0.012. The health sector, especially nursing, is expected to be able to apply progressive muscle relaxation techniques and natural sound music therapy to reduce stress levels.